2011
DOI: 10.1080/00958964.2010.547230
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Academic Major and Environmentalism Among College Students: Is it Mediated by the Effects of Gender, Political Ideology and Financial Security?

Abstract: Several studies have found a relationship between college students' academic majors and their environmental attitudes and behaviors. Results from this study of incoming first-year students at a medium-sized public university suggest that students majoring in different programs of study were likely to have different environmental attitudes and behaviors. There were also differences in the proportions of women, political liberals, and financially secure students in each of the different majors. When controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 24 publications
7
28
0
Order By: Relevance
“…They note that virtually all relevant studies have found that politically liberal actors (individuals) have higher degrees of social concern than politically conservative people. This is, in part, because conservatives generally maintain a pro-business mindset, they endorse the idea of limited (laissez-faire) government and because they are likely to be cautious about social change (Lang, 2011). According to Shriberg (2002), those institutions which are perceived to be liberal and progressive tend to be more responsive to social and environmental concerns than those perceived to be conservative.…”
Section: Political Orientationmentioning
confidence: 95%
See 1 more Smart Citation
“…They note that virtually all relevant studies have found that politically liberal actors (individuals) have higher degrees of social concern than politically conservative people. This is, in part, because conservatives generally maintain a pro-business mindset, they endorse the idea of limited (laissez-faire) government and because they are likely to be cautious about social change (Lang, 2011). According to Shriberg (2002), those institutions which are perceived to be liberal and progressive tend to be more responsive to social and environmental concerns than those perceived to be conservative.…”
Section: Political Orientationmentioning
confidence: 95%
“…Each regional government plays an important role in funding public universities in Spain. Based on previous studies, it could be inferred that Spanish public universities located in those regions which have been managed by politically liberal governing bodies would implement more sustainability practices as a response to the greater social concerns of liberal and progressive governors (Lang, 2011;Shriberg, 2002).…”
Section: Political Orientationmentioning
confidence: 99%
“…Studies of college students portray a population that typically demonstrates higher pro-environmental attitudes and behaviors (Cordano et al 2011;Dunlap et al 2000;Lang 2011;Levine and Strube 2012;Thapa 1999). A growing number of universities offer courses that focus on environmental issues, employ various environmental initiatives, and provide facilities for recycling and energy conservation.…”
Section: Forms Of Environmental Behaviormentioning
confidence: 98%
“…We focus on four individual-level predictors that have been identified in previous philanthropic and environmental research: environmental concern, environmental knowledge, pro-social behavior, and socio-demographic characteristics (e.g., Bekkers and Wiepking 2011;Lang 2011;Lévy-Leboyer et al 1996). Figure 1 presents these various elements in our model.…”
Section: Correlates Of Students' Environmental Behaviormentioning
confidence: 98%
“…Such studies point to prior family experiences, including time spent outdoors, and broader family norms as important determinants of environmental friendly behaviors among emerging adults (Sivek 2002;Grønhøj and Thøgersen 2012). A study of incoming first year college students in central Pennsylvania revealed that subject major can also influence environmental attitudes and behaviors (Lang 2011). A study on the relative importance and perceptions of environmental issues among Cornell University students showed that a willingness to take action does not vary between environmental issues; students ranked environmental issues as equal in importance (Gigliotti 1994).…”
Section: Introductionmentioning
confidence: 99%